2011
DOI: 10.1007/s11523-011-0198-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeted agents: review of toxicity in the elderly metastatic colorectal cancer patients

Abstract: Colorectal cancer remains a major cause of cancer mortality in the Western world. With a median age at presentation of 71, patients with metastatic disease are often elderly with significant co-morbidities. In addition, elderly patients are more likely to be undertreated and under-represented in clinical trials. Therefore, as the available data from clinical trials are scarce, the optimal treatment strategy for this group of patients has not been adequately defined. In the setting of metastatic colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Moreover, the incidence of hypertension was also found to be age-related [22]. Bleeding, gastrointestinal perforations, and wound healing complications were observed less often [23]. In the present study, the above mentioned adverse events were recorded less frequently than in previously reported (Table 4).…”
Section: Discussionsupporting
confidence: 47%
“…Moreover, the incidence of hypertension was also found to be age-related [22]. Bleeding, gastrointestinal perforations, and wound healing complications were observed less often [23]. In the present study, the above mentioned adverse events were recorded less frequently than in previously reported (Table 4).…”
Section: Discussionsupporting
confidence: 47%
“…Furthermore, older patients who are treated with chemotherapy are at high risk for adverse outcomes, including chemotherapy toxicity and functional and physical consequences ( 19 21 ). In addition, older adults are more susceptible to toxicity from combination chemotherapy plus newer immunotherapy or targeted kinase inhibitors ( 22 25 ). In a randomized controlled trial by Corre et al, GA-guided lung cancer treatment strategies have been shown to lower symptomatic toxicities and improve other clinical outcomes among older adults receiving chemotherapy for advanced lung cancer ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…The management of colorectal cancer has evolved into a truly multidisciplinary model. Several studies suggest that the types of treatment modalities used, the order in which they are applied as well as the particular combinations of therapies influence outcomes depending upon tumour factors including the anatomical segment involved and the location and extent of disease, whether previous treatments were used and patient‐related factors. Deviations from treatment guidelines have an adverse influence on the outcome for colorectal cancer .…”
mentioning
confidence: 99%